Prevalence of factor V Leiden, prothrombin G20210A, and MTHFR C677T mutations in a Greek population of blood donors - Antoniadi,T.; Hatzis,T.; Kroupis, C.; Economou-Petersen,E.; Petersen, MB (Am.J.Hematol., 1999)
The pathogenesis of venous thrombosis involves the interaction of genetic and environmental factors. In order to estimate the frequency of the factor V Leiden, the prothrombin G20210A, and the MTHFR C677T mutations in the Greek population, we analyzed 160 healthy Greek blood donors by PCR amplification and detected allele frequencies of 2.5%, 2.2%, and 35.3%, respectively. The allele frequencies were compared with reported frequencies of other populations of southern Europe. The identification of these common genetic risk factors for thrombosis should enable easy DNA diagnosis and carrier detection in a high proportion of cases and will contribute to a better understanding of the interaction of genetic and environmental risk factors
DA - 19990902 IS - 0361-8609 (Print) IS - 0361-8609 (Linking) LA - eng PT - Comparative Study PT - Journal Article RN - 0 (factor V Leiden) RN - 9001-24-5 (Factor V) RN - 9001-26-7 (Prothrombin) RN - EC 1.5.- (Oxidoreductases Acting on CH-NH Group Donors) RN - EC 1.5.1.20 (Methylenetetrahydrofolate Reductase (NADPH2)) SB - IM
Keywords: Adult; Alleles; Blood; Blood Donors; Diagnosis; Etiology; Europe; Factor V; Female; Gene Frequency; genetics; Greece; Heterozygote Detection; Humans; isolation & purification; Male; Methylenetetrahydrofolate Reductase (NADPH2); Middle Aged; Oxidoreductases Acting on CH-NH Group Donors; Point Mutation; polymerase chain reaction; Prevalence; Prothrombin; Risk Factors; Venous Thrombosis